Transcervical Mediastinoscopic Closure of Left-Sided Postpneumonectomy Bronchial Stump Fistula - Paleru, Cristian; Cordoş, Ioan; Dănăilă, Olga; Bolca, Ciprian (The Thoracic and Cardiovascular Surgeon, 2019)
Introduction This article presents a series of patients on which the transcervical approach was used to close a left-sided postpneumonectomy fistula.Materials and Methods The series comprises nine patients with a left pneumonectomy performed for a tuberculosis-related suppurative disease in five cases and for lung cancer in the remaining four. This procedure can be performed under certain conditions, the most important one being the length of the bronchial stump, which should be at least 1 cm, ideally 1.5 cm. The transcervical stump closure was successfully achieved in all patients, having been more technically demanding in cancer cases with previous lymphadenectomy. The postpneumonectomy infected cavity was subsequently treated.Results The follow-up continued for at least 1 year; one individual from the cancer patients group died from an uncontrolled sepsis during the postoperative period, another one died 17 months later from metastatic cancer and two of them are alive, with no signs of neoplastic or infectious relapse 15 and 37 months, respectively, after the cervical procedure. One patient from the suppurative disease group had a relapse of the fistula 2 months after surgery, requiring additional surgical procedures to deal with this issue; all the other patients are alive, with no signs of recurrence.Conclusions The transcervical approach is a very suitable maneuver in selected patients with a bronchial stump at least 1 cm long, ideally 1.5 cm.
Keywords: airway; bronchial disease; mediastinum